Mechanisms of infection with Epstein-Barr virus. I. Viral DNA replication and formation of noninfectious virus particles in superinfected Raji cells. - Yajima, Y (1976)
Human lymphoblastoid Raji cells, which do not produce virus, supported replication of Epstein-Barr virus (EBV) upon superinfection. Early antigen, viral capsid antigen, and virions were produced in Raji cells superinfected with EBV. Viral DNA replicated under complete inhibition of host cell DNA synthesis to the extent that a few micrograms of EBV DNA were recovered from 107 superinfected Raji cells, corresponding to 5,000 viral genomes/cell. Homology of the synthesized viral DNA to parental EBV DNA was more than 90%. Virions produced by the Raji cells contained a 55S DNA but failed to induce early antigen, viral capsid antigen, and viral DNA synthesis after a second superinfection of Raji cells.